Analisis Pengendalian Intern Piutang Usaha Pada PT. ANI Unit Percetakan Arnoldus Ende - Leda, Maria Hariati; Londa, Yulita; Banda, Falentina L (Jurnal Riset Ilmu Akuntansi, 2021)
This research is to analyze the Accounts Receivable Internal Control at PT. ANI Arnoldus Ende Printing Unit. The research method used is descriptive qualitative research methods. Sources of data in this study are using primary and secondary data. The results achieved in this study are to show that the company's internal control for trade receivables actually exists, but it does not function properly which can be seen in the inefficient internal control procedures for providing accounts receivable. During the initial process, the internal control procedure for giving accounts receivable, which checks customer credit data, should have been carried out by the sales department. At the stage of delivery of ordered goods or finished goods it should be done by the shipping department, but at PT. ANI Arnoldus Printing unit is carried out by the Production Department. Approval of accounts receivable is carried out by company managers, but in the organizational structure there is an internal control team (budget), where in this study the main tasks and functions of the internal supervisory team (budget) are not visible.